Behavior of steel fiber reinforced concrete beams with CFRP wrapped lap splice bars. (October 2022) - Al-Mamory, Zainab Kareem; Al-Ahmed, Ali Hussein Ali
Abstract: This research employed an experimental and numerical investigation of a new method for over-lap splicing rebar employing an epoxy resin-coated carbon fiber-reinforced polymer (CFRP) sheet to enhance the behavior of the splice tension bars. The normal concrete strength with Steel fiber mix were prepared for casting seven specimens for this purpose, and tested under monotonic, four-point bending load conditions. three of the specimens were made of CFRP over-lap splice in addition to three traditional lap-splice beams, with one specimen as a reference with full length continuous bar. In addition, three ratios of lapping length were studied, they are; 33%, 66%, and 100% for each type of splice. The used percentage of steel fiber (SF) was equal to 0.5% by mix volume. It was noticed a significant enhancement in the behavior and flexural strength with the use of CFRP over-lap splice as compared with the traditional lap splice. Moreover, this approach was simulated numerically by using Abaqus software. The simulation resulted according to the adopted criteria showed good agreement to the results of the work that was done in the lab.